2013
DOI: 10.1134/s000629791302003x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of T-cell anergy

Abstract: Anergy is a long-term stable state of T-lymphocyte unresponsiveness to antigenic stimulation associated with the blockade of IL-2 production and proliferation. Anergy is a pathway of peripheral tolerance formation. In this review, mechanisms underlying T-cell tolerization are considered in a classical in vitro model of clonal anergy, and these mechanisms are compared with different pathways of anergy induction in vivo. Special attention is given to regulatory T-lymphocytes because, on one hand, anergy is a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 155 publications
0
18
0
Order By: Relevance
“…Other signals required for T cell activation include costimulatory molecules, e.g., CD80 and CD86 (2325). T cells that receive signals only via TCR by engagement with MHC-peptide complex, without receiving the second signal from costimulatory ligands, are destined to undergo anergy (26). Moreover, the local cytokine niche determines the type of T cell response generated.…”
Section: Discussionmentioning
confidence: 99%
“…Other signals required for T cell activation include costimulatory molecules, e.g., CD80 and CD86 (2325). T cells that receive signals only via TCR by engagement with MHC-peptide complex, without receiving the second signal from costimulatory ligands, are destined to undergo anergy (26). Moreover, the local cytokine niche determines the type of T cell response generated.…”
Section: Discussionmentioning
confidence: 99%
“…5C highlights several genes relevant for activation, proliferation, and homeostasis of T cells that were significantly up-or downregulated through IL-7 treatment in DN T cells. Of interest, we found that predominantly genes that are necessary for maintaining an anergic state (30)(31)(32)(33) are downregulated in IL-7-treated DN T cells. The abrogated expression of anergy-controlling factors, such as FOXO, NFAT, EGR2, EGR3, and CBL, was verified by quantitative PCR (Fig.…”
Section: Transcriptome Analysis Identifies Key Downstream Network Ofmentioning
confidence: 96%
“…Because increased intracellular Ca 2+ levels in the absence of complete TCR signals are known to activate NFAT1, which can then activate anergy-inducing genes, we hypothesized that the reduced functionality of mir-150 −/− naïve CD8 + T cells might be associated with ectopic activation of NFAT1 in naïve mir-150 −/− CD8 + T cells 2, 5, 15 . Following incubation in physiological Ca 2+ concentrations, naïve mir-150 −/− CD8 + T cells showed increased nuclear localization of NFAT1 and active forms of NFAT1 (dephosphorylated NFAT1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TCR stimulation increases intracellular Ca 2+ concentrations, which induce the nuclear localization of nuclear factor of activated T-cells 1 (NFAT1) 2 . Simultaneously, CD28 co-stimulation activates mitogen-activated protein kinase, which activates activator protein 1 (AP-1).…”
Section: Introductionmentioning
confidence: 99%